AUTOMATIC SPEECH RECOGNITION (ASR) BASED ON PROGRESSIVE WEB APPS TO DEVELOP PRONUNCIATION LEARNING - Iqbal, Muhammad (Universitas Royal, 2024)
Abstract: Good pronunciation plays a crucial role in enhancing students' confidence, encouraging active participation in learning, and preparing them for academic and professional opportunities, such as English-language interviews. Poor pronunciation during scholarship or job interviews can hinder the interviewer's understanding, thereby reducing the chances of acceptance. This study aims to improve students' pronunciation fluency and develop a learning medium based on Automatic Speech Recognition (ASR) technology. The method employed involves the development of Progressive Web Apps (PWA) integrated with ASR technology from the app.lumi.education platform, supported by manual labeling for pronunciation validation. The research was conducted at LKP Vijaya Learning Centre, Tanjungbalai City. The results demonstrate that ASR-based media significantly enhances students' pronunciation accuracy and confidence. Thus, the integration of ASR technology into PWA effectively supports innovative and efficient pronunciation learning. Keywords: automatic speech recognition; language learning; pronunciation; web-based application. Abstrak: Pengucapan yang baik berperan penting dalam meningkatkan kepercayaan diri siswa, mendorong partisipasi aktif dalam pembelajaran, dan mempersiapkan mereka menghadapi peluang akademik maupun profesional, seperti wawancara berbahasa Inggris. saat menghadapi wawancara beasiswa atau pekerjaan berbahasa Inggris, pengucapan yang buruk dapat mengurangi pemahaman pewawancara, sehingga mengurangi peluang diterima. Penelitian ini bertujuan untuk meningkatkan kelancaran pengucapan siswa dan mengembangkan media pembelajaran berbasis teknologi Automatic Speech Recognition (ASR). Metode yang digunakan adalah pengembangan Progressive Web Apps (PWA) yang terintegrasi dengan ASR dari aplikasi app.lumi.education, didukung oleh pelabelan manual untuk validasi pengucapan. Penelitian dilakukan di LKP Vijaya Learning Centre, Kota Tanjungbalai. Hasil penelitian menunjukkan bahwa media berbasis ASR secara signifikan meningkatkan akurasi pengucapan dan kepercayaan diri siswa. Dengan demikian, integrasi teknologi ASR dalam PWA terbukti mendukung pembelajaran pengucapan secara inovatif dan efisien.Kata kunci: aplikasi berbasis web; pengenalan suara otomatis; pembelajaran bahasa; pengucapan